Cathelicidin-inspired antimicrobial peptides as novel antifungal compounds. (1st April 2020) - van Eijk, Martin; Boerefijn, Stephanie; Cen, Lida; Rosa, Marisela; Morren, Marnix J H; van der Ent, Cornelis K; Kraak, Bart; Dijksterhuis, Jan; Valdes, Ivan D; Haagsman, Henk P; de Cock, Hans
Abstract: Fungal infections in humans are increasing worldwide and are currently mostly treated with a relative limited set of antifungals. Resistance to antifungals is increasing, for example, in Aspergillus fumigatus and Candida auris, and expected to increase for many medically relevant fungal species in the near future. We have developed and patented a set of cathelicidin-inspired antimicrobial peptides termed 'PepBiotics'. These peptides were initially selected for their bactericidal activity against clinically relevant Pseudomonas aeruginosa and Staphylococcus aureus isolates derived from patients with cystic fibrosis and are active against a wide range of bacteria (ESKAPE pathogens). We now report results from studies that were designed to investigate the antifungal activity of PepBiotics against a set of medically relevant species encompassing species of Aspergillus, Candida, Cryptococcus, Fusarium, Malassezia, and Talaromyces . We characterized a subset of PepBiotics and show that these peptides strongly affected metabolic activity and/or growth of a set of medically relevant fungal species, including azole-resistant A. fumigatus isolates. PepBiotics showed a strong inhibitory activity against a large variety of filamentous fungi and yeasts species at low concentrations (≤1 μM) and were fungicidal for at least a subset of these fungal species. Interestingly, the concentration of PepBiotics required to interfere with growth or metabolic activity varied between different fungal species or even between isolates of the same fungal species. This study shows that PepBiotics display strong potential for use as novel antifungal compounds to fight a large variety of clinically relevant fungal species.